A CONSTRUÇÃO DO PROJETO POLÍTICO PEDAGÓGICO NUMA PERSPECTIVA DEMOCRÁTICA: UMA EXPERIÊNCIA NA REDE MUNICIPAL DE ENSINO EM SANTO ANDRÉ, SP - Silva, Deise de Oliveira da (2009)
This paper deals with the efforts for the Santo André (SP) municipal school net democratization and the public policies implemented for the achievement of that goal from 1997 to 2008, focusing on the political pedagogical project construction as democratic alternative and trying to identify the creation of mechanisms that supported this construction. With a qualitative character, the research developed a fieldwork ruled by the investigation of documents published in that period, conducted interviews, applied questionnaires and used focal groups, so that data provided a theoretic reflection and a dialogic analysis on the chosen thematic. A bibliographical study was founded on the ideas of Antonio Gramsci, the cultural hegemony theorist, who inspired the democratization-bound march. All the wa y long, this research tries to find a counter-hegemonic movement that signalizes possible changes in school and its contribution to a democratic space construction. The elaboration, following and evaluation of the political pedagogical project as a dialog reference are discussed on the grounds of "deal quality" concept, with Luiz Carlos de Freitas contributions. Another resource was the contributions of academically acknowledged authors with researches on the same subject, exposing the contradictory and conflictive dynamics for participative processes instauration, in a country withauthoritarian tradition such as Brazil. Data analysis allowed presenting and recognizing the boundaries of school management, historically centralized and hierarchical, observing in the process the creation of participating mechanisms for the construction of a new school management culture. The research elucidates the importance of a sociability place construction a place of struggle, according Gramsci, and of frontier, according Freitas , a space that allows the creation of social action possibilities constructed by both political and civil societies.(AU0